Extracted water soluble polysaccharide from gum Arabic as potential prebiotic - Hammad, Ahallil; Abdullah, Aminah; Sarbini, Shahrul Razid; Maskat, Mohamad Yusof (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Gum Arabic (GA) is the dried gummy exudates obtained from stems and branches of trees of selected Acacia species (Acacia senegal & Acacia seyal). Present study includes extraction of water soluble polysaccharide of Gum Arabic from two different species. Polysaccharide was obtained by aqueous extraction, this methodology is simpler to perform than other existing extraction and purification methodologies, and because it avoids the use of organic solvents (other than ethanol). The characterized of isolated polysaccharide was defined by FTIR spectrum. The polysaccharide was characterized by the measurement of total sugar and reducing groups using phenol sulfuric method and DNS assay respectively. The crude polysaccharides were further studied by measuring protein and fat content. The digestibility of polysaccharides by human gastric juice was also determined. The vibrational assignment of the bands observed in FTIR spectrum is verified. The broad peak appeared at 950-1200 range indicate the finger print of polysaccharide. Results revealed the average values of proteins; 1.8% to 0.78% and fat; 0%. Acacia Senegal and Acacia Seyal showed great resistance towards artificial human gastric juice. The current study reveals that the extraction using aqueous extraction eliminates the protein content, thus providing more pure polysaccharide suitable for biological applications. The results also confirm the suitability of the extracted polysaccharide obtain from (Acacia Senegal & Acacia Seyal) to resist toward acid digestibility.